2018
DOI: 10.1016/j.bbrep.2018.10.014
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Doublecortin-like kinase 1 compromises DNA repair and induces chromosomal instability

Abstract: Doublecortin-like kinase 1 (DCLK1) is a serine/threonine-kinase with two doublecortin (DCX) domains. DCLK1 is associated with microtubules via DCX domains and regulates microtubule polymerization. DCLK1 is known to be expressed in cancer stem cells and provides cancer cells with tumor-initiating capacity. Accumulating clinical evidence supports that DCLK1 is associated with tumor aggressiveness and is an important prognostic marker in various human cancers. However, the mechanism, by which DCLK1 causes oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, we noticed that the doublecortin-like kinase DCLK1 (also known as DCAMKL1) is enriched in our BioIDs under replication stress. Various studies have demonstrated the importance of DCLK1 during the DNA damage response [47,48], and our data suggest that DCLK1 may play a role in the regulation of the classical RAD51 paralogs during the response to replication stress.…”
Section: Plos Geneticssupporting
confidence: 62%
“…Interestingly, we noticed that the doublecortin-like kinase DCLK1 (also known as DCAMKL1) is enriched in our BioIDs under replication stress. Various studies have demonstrated the importance of DCLK1 during the DNA damage response [47,48], and our data suggest that DCLK1 may play a role in the regulation of the classical RAD51 paralogs during the response to replication stress.…”
Section: Plos Geneticssupporting
confidence: 62%
“…It was suggested that DCLK1 regulates migration, invasion and cell motility via activation of EMT (43), an important process for cancer initiation, cancer metastasis, and secondary tumor formation. However, expression of DCLK1 was also associated with impaired DNA repair (57,58), upregulation of WNT/b-catenin (59,60), RAS (13,61), PI3K/AKT (62) and VEGF (63,64) signaling, suggesting a multifaceted role of DCLK1 in cancer initiation and progression. Concordantly, our analysis of TCGA-HNSC dataset indicates that in HNSCC, tumors expressing higher DCLK1 mRNA levels were enriched for pathways that have been implicated in the EMT and CSC maintenance (such as NOTCH, WNT, TGFb, and hedgehog signaling), as well as for RAS and angiogenesis cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the temporal and spatial expression pattern of doublecortin is very similar to that of DCLK1, DCLK1 is proposed to have functions similar to that of doublecortin ( 20 , 21 ). Thus, it may serve a role in neuronal migration, axon transport, synapse maturation and brain development ( 21 24 ). Furthermore, DCLK1 has two isoforms of varying lengths because of the epithelial changes that occur with different functions, where the shorter isoform DCLK1-S induces tumorigenesis in colorectal cancer (CRC) ( 7 , 25 , 26 ).…”
Section: Functions Of Dclk1 and Its Role In Cancermentioning
confidence: 99%